Nonmonotonic energy dependence of net-proton number fluctuations - STAR Collaboration (Physical Review Letters, 2021)
Nonmonotonic variation with collision energy (sNN) of the moments of the net-baryon number distribution in heavy-ion collisions, related to the correlation length and the susceptibilities of the system, is suggested as a signature for the quantum chromodynamics critical point. We report the first evidence of a nonmonotonic variation in the kurtosis times variance of the net-proton number (proxy for net-baryon number) distribution as a function of sNN with 3.1 σ significance for head-on (central) gold-on-gold (Au+Au) collisions measured solenoidal tracker at Relativistic Heavy Ion Collider. Data in noncentral Au+Au collisions and models of heavy-ion collisions without a critical point show a monotonic variation as a function of sNN. © 2021 American Physical Society.
Keywords: Colliding beam accelerators; Collision energies; Correlation lengths; Gold; Hadrons; Heavy ion collision; Heavy ions; Ion sources; Monotonic variations; Non-monotonic variation; Number fluctuations; Quantum chromodynamics; Quantum theory; Relativistic Heavy Ion Collider; dept.phy; peer-reviewed

Measurements of W and Z /γ∗ cross sections and their ratios in p+p collisions at RHIC - STAR Collaboration (Physical Review D, 2021)
We report on the W and Z/γ∗ differential and total cross sections as well as the W+/W− and (W++W−)/(Z/γ∗) cross section ratios measured by the STAR experiment at RHIC in p+p collisions at √s=500 GeV and 510 GeV. The cross sections and their ratios are sensitive to quark and antiquark parton distribution functions. In particular, at leading order, the W cross section ratio is sensitive to the ¯d/¯u ratio. These measurements were taken at high Q2∼M2W,M2Z and can serve as input into global analyses to provide constraints on the sea quark distributions. The results presented here combine three STAR datasets from 2011, 2012, and 2013, accumulating an integrated luminosity of 350 pb−1. We also assess the expected impact that our W+/W− cross section ratios will have on various quark distributions, and find sensitivity to the ¯u−¯d and ¯d/¯u distributions.
Keywords: dept.phy; peer-reviewed

Observation of Ds± /D0 enhancement in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
We report on the first measurement of charm-strange meson Ds± production at midrapidity in Au+Au collisions at sNN=200 GeV from the STAR experiment. The yield ratio between strange (Ds±) and nonstrange (D0) open-charm mesons is presented and compared to model calculations. A significant enhancement, relative to a pythia simulation of p+p collisions, is observed in the Ds±/D0 yield ratio in Au+Au collisions over a large range of collision centralities. Model calculations incorporating abundant strange-quark production in the quark-gluon plasma and coalescence hadronization qualitatively reproduce the data. The transverse-momentum integrated yield ratio of Ds±/D0 at midrapidity is consistent with a prediction from a statistical hadronization model with the parameters constrained by the yields of light and strange hadrons measured at the same collision energy. These results suggest that the coalescence of charm quarks with strange quarks in the quark-gluon plasma plays an important role in Ds±-meson production in heavy-ion collisions. © 2021 authors. Published by the American Physical Society. Funded by SCOAP3.
Keywords: Au+Au collisions; Bosons; Coalescence; Colliding beam accelerators; Collision energies; Collisional plasmas; Germanium compounds; Gold compounds; Hadrons; Heavy ion collision; Heavy ions; Meson production; Model calculations; Quantum theory; Quark production; Quark-gluon plasma; Transverse momenta; dept.phy; peer-reviewed

Measurement of e+e- momentum and angular distributions from linearly polarized photon collisions - STAR Collaboration (Physical Review Letters, 2021)
The Breit-Wheeler process which produces matter and antimatter from photon collisions is experimentally investigated through the observation of 6085 exclusive electron-positron pairs in ultraperipheral Au+Au collisions at sqrt[s_{NN}]=200 GeV. The measurements reveal a large fourth-order angular modulation of cos4DELTAphi=(16.8+/-2.5)% and smooth invariant mass distribution absent of vector mesons (phi, omega, and rho) at the experimental limit of <=0.2% of the observed yields. The differential cross section as a function of e^{+}e^{-} pair transverse momentum P_{} peaks at low value with sqrt[ ]=38.1+/-0.9 MeV and displays a significant centrality dependence. These features are consistent with QED calculations for the collision of linearly polarized photons quantized from the extremely strong electromagnetic fields generated by the highly charged Au nuclei at ultrarelativistic speed. The experimental results have implications for vacuum birefringence and for mapping the magnetic field which is important for emergent QCD phenomena.
Keywords: Angular distribution; Angular-modulation; Au+Au collisions; Colliding beam accelerators; Differential cross section; Electron-positron pairs; Invariant mass distribution; Linearly polarized; Matter and antimatters; Photons; Transverse momenta; dept.phy; peer-reviewed

Global polarization of ξ and ω hyperons in au+au collisions at sNN =200 GeV - STAR Collaboration (Physical Review Letters, 2021)
Global polarization of Ξ and ω hyperons has been measured for the first time in Au+Au collisions at sNN=200 GeV. The measurements of the Ξ- and Ξ¯+ hyperon polarization have been performed by two independent methods, via analysis of the angular distribution of the daughter particles in the parity violating weak decay Ξ→Λ+π, as well as by measuring the polarization of the daughter Λ hyperon, polarized via polarization transfer from its parent. The polarization, obtained by combining the results from the two methods and averaged over Ξ- and Ξ¯+, is measured to be ⟨PΞ ©=0.47±0.10(stat)±0.23(syst)% for the collision centrality 20%-80%. The ⟨PΞ. © 2021 American Physical Society. All rights reserved.
Keywords: Angular distribution; Au+Au collisions; Colliding beam accelerators; Global polarizations; Hyperon polarization; Measurements of; Polarization; Polarization transfer; dept.phy; peer-reviewed

Methods for a blind analysis of isobar data collected by the STAR collaboration - STAR Collaboration (Nuclear Science and Techniques, 2021)
Keywords: Au+Au collisions; Calculating efficiencies; Colliding beam accelerators; Data challenges; Germanium compounds; Gold; Magnetic effects; Nitrogen compounds; Quality assurance; Quality control; Ruthenium compounds; Species specifics; Stars; Time dependent; Time-dependent changes; Tuning analysis; Zirconium compounds; dept.phy; peer-reviewed

Comparison of transverse single-spin asymmetries for forward π0 production in polarized pp, pAl and pAu collisions at nucleon pair c.m. energy sNN =200 GeV - STAR Collaboration (Physical Review D, 2021)
The STAR collaboration reports a measurement of the transverse single-spin asymmetries, AN, for neutral pions produced in polarized proton collisions with protons (pp), with aluminum nuclei (pAl) and with gold nuclei (pAu) at a nucleon-nucleon center-of-mass energy of 200 GeV. Neutral pions are observed in the forward direction relative to the transversely polarized proton beam, in the pseudorapidity region 2.7<η<3.8. Results are presented for π0s observed in the STAR forward meson spectrometer electromagnetic calorimeter in narrow Feynman x (xF) and transverse momentum (pT) bins, spanning the range 0.17<xF<0.81 and 1.7<pT<6.0 GeV/c. For fixed xF<0.47, the asymmetries are found to rise with increasing transverse momentum. For larger xF, the asymmetry flattens or falls as pT increases. Parametrizing the ratio r(A)≡AN(pA)/AN(pp)=AP over the kinematic range, the ratio r(A) is found to depend only weakly on A, with ⟨P⟩=−0.027±0.005. No significant difference in P is observed between the low-pT region, pT<2.5 GeV/c, where gluon saturation effects may play a role, and the high-pT region, pT>2.5 GeV/c. It is further observed that the value of AN is significantly larger for events with a large-pT isolated π0 than for events with a nonisolated π0 accompanied by additional jetlike fragments. The nuclear dependence r(A) is similar for isolated and nonisolated π0 events.
Keywords: dept.phy; peer-reviewed

Measurement of transverse single-spin asymmetries of π 0 and electromagnetic jets at forward rapidity in 200 and 500 GeV transversely polarized proton-proton collisions - STAR Collaboration (Physical Review D, 2021)
The STAR Collaboration reports measurements of the transverse single-spin asymmetry (TSSA) of inclusive π0 at center-of-mass energies (√s) of 200 GeV and 500 GeV in transversely polarized proton-proton collisions in the pseudo-rapidity region 2.7 to 4.0. The results at the two different energies show a continuous increase of the TSSA with Feynman-x, and, when compared to previous measurements, no dependence on √s from 19.4 GeV to 500 GeV is found. To investigate the underlying physics leading to this large TSSA, different topologies have been studied. π0 with no nearby particles tend to have a higher TSSA than inclusive π0. The TSSA for inclusive electromagnetic jets, sensitive to the Sivers effect in the initial state, is substantially smaller, but shows the same behavior as the inclusive π0 asymmetry as a function of Feynman-x. To investigate final-state effects, the Collins asymmetry of π0 inside electromagnetic jets has been measured. The Collins asymmetry is analyzed for its dependence on the π0 momentum transverse to the jet thrust axis and its dependence on the fraction of jet energy carried by the π0. The asymmetry was found to be small in each case for both center-of-mass energies. All the measurements are compared to QCD-based theoretical calculations for transverse-momentum-dependent parton distribution functions and fragmentation functions. Some discrepancies are found, which indicates new mechanisms might be involved.
Keywords: dept.phy; peer-reviewed

Azimuthal anisotropy measurements of strange and multistrange hadrons in U+ U collisions at sNN =193 GeV at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2021)
We present systematic measurements of azimuthal anisotropy for strange and multistrange hadrons (K0s, Λ, Ξ, and Ω) and ϕ mesons at midrapidity (|y|< 1.0) in collisions of U+U nuclei at √sNN=193 GeV, recorded by the STAR detector at the Relativistic Heavy Ion Collider. Transverse momentum (pT) dependence of flow coefficients (v2, v3, and v4) is presented for minimum bias collisions and three different centrality intervals. Number of constituent quark scaling of the measured flow coefficients in U+U collisions is discussed. We also present the ratio of vn scaled by the participant eccentricity (ɛn{2}) to explore system size dependence and collectivity in U+U collisions. The magnitude of v2/ɛ2 is found to be smaller in U+U collisions than that in central Au+Au collisions contradicting naive eccentricity scaling. Furthermore, the ratios between various flow harmonics (v3/v3/22, v4/v4/22) are studied and compared with hydrodynamic and transport model calculations.
Keywords: dept.phy; peer-reviewed

Cumulants and correlation functions of net-proton, proton, and antiproton multiplicity distributions in Au + Au collisions at energies available at the BNL Relativistic Heavy Ion Collider - STAR Collaboration (Physical Review C, 2021)
We report a systematic measurement of cumulants, Cn, for net-proton, proton, and antiproton multiplicity distributions, and correlation functions, κn, for proton and antiproton multiplicity distributions up to the fourth order in Au+Au collisions at √sNN=7.7, 11.5, 14.5, 19.6, 27, 39, 54.4, 62.4, and 200 GeV. The Cn and κn are presented as a function of collision energy, centrality and kinematic acceptance in rapidity, y, and transverse momentum, pT. The data were taken during the first phase of the Beam Energy Scan (BES) program (2010–2017) at the BNL Relativistic Heavy Ion Collider (RHIC) facility. The measurements are carried out at midrapidity (|y|< 0.5) and transverse momentum 0.4<pT<2.0GeV/c, using the STAR detector at RHIC. We observe a nonmonotonic energy dependence (√sNN = 7.7–62.4 GeV) of the net-proton C4/C2 with the significance of 3.1σ for the 0–5% central Au+Au collisions. This is consistent with the expectations of critical fluctuations in a QCD-inspired model. Thermal and transport model calculations show a monotonic variation with √sNN. For the multiparticle correlation functions, we observe significant negative values for a two-particle correlation function, κ2, of protons and antiprotons, which are mainly due to the effects of baryon number conservation. Furthermore, it is found that the four-particle correlation function, κ4, of protons plays a role in determining the energy dependence of proton C4/C1 below 19.6 GeV, which cannot be understood by the effect of baryon number conservation.
Keywords: dept.phy; peer-reviewed

Flow and interferometry results from Au+Au collisions at sNN =4.5 GeV - STAR Collaboration (Physical Review C, 2021)
The beam energy scan (BES) program at the BNL Relativistic Heavy Ion Collider (RHIC) was extended to energies below √sNN=7.7 GeV in 2015 by successful implementation of the fixed-target mode of operation in the STAR (Solenoidal Tracker At RHIC) experiment. In this mode, ions circulate in one ring of the collider and interact with a stationary target at the entrance of the STAR time projection chamber. The first results for Au+Au collisions at √sNN=4.5 GeV are presented, demonstrating good performance of all the relevant detector subsystems in fixed-target mode. Results presented here include directed and elliptic flow of identified hadrons, and radii from pion femtoscopy. The latter, together with recent HADES results, reveal a long-sought peak structure that may be caused by the system evolving through a first-order phase transition from quark-gluon plasma to the hadronic phase. Directed and elliptic flow for pions are presented for the first time at this beam energy. Pion and proton elliptic flow show behavior which hints at constituent quark scaling, and demonstrate that a definitive conclusion will be achievable using the full statistics of the ongoing second phase of BES (BES-II). In particular, BES-II to date has recorded fixed-target data sets with two orders of magnitude more events at each of nine energies between √sNN=3.0 and 7.7 GeV.
Keywords: dept.phy; peer-reviewed

Invariant jet mass measurements in pp collisions at s =200 GeV at RHIC - STAR Collaboration (Physical Review D, 2021)
We present the first inclusive measurements of the invariant and softdrop jet mass in proton-proton collisions at √s=200 GeV at STAR. The measurements are fully corrected for detector effects, and reported differentially in both the jet transverse momentum and jet radius parameter. We compare the measurements to established leading-order Monte Carlo event generators and find that STAR-tuned pythia-6 reproduces the data, while LHC tunes of pythia-8 and herwig-7 do not agree with the data, providing further constraints on parameter tuning. Finally, we observe that softdrop grooming, for which the contribution of wide-angle nonperturbative radiation is suppressed, shifts the jet mass distributions into closer agreement with the partonic jet mass as determined by both pythia-8 and a next-to-leading-logarithmic accuracy perturbative QCD calculation. These measurements complement recent LHC measurements in a different kinematic region, as well as establish a baseline for future jet mass measurements in heavy-ion collisions at RHIC.
Keywords: dept.phy; peer-reviewed

Longitudinal double-spin asymmetry for inclusive jet and dijet production in polarized proton collisions at s =200 GeV - STAR Collaboration (Physical Review D, 2021)
We report high-precision measurements of the longitudinal double-spin asymmetry, ALL, for midrapidity inclusive jet and dijet production in polarized pp collisions at a center-of-mass energy of √s=200 GeV. The new inclusive jet data are sensitive to the gluon helicity distribution, Δg(x,Q2), for gluon momentum fractions in the range from x≃0.05 to x≃0.5, while the new dijet data provide further constraints on the x dependence of Δg(x,Q2). The results are in good agreement with previous measurements at √s=200 GeV and with recent theoretical evaluations of prior world data. Our new results have better precision and thus strengthen the evidence that Δg(x,Q2) is positive for x>0.05.
Keywords: dept.phy; peer-reviewed

Measurement of the sixth-order cumulant of net-proton multiplicity distributions in au+au collisions at s NN =27, 54.4, and 200 GeV at RHIC - STAR Collaboration (Physical Review Letters, 2021)
According to first-principle lattice QCD calculations, the transition from quark-gluon plasma to hadronic matter is a smooth crossover in the region μB≤Tc. In this range the ratio, C6/C2, of net-baryon distributions are predicted to be negative. In this Letter, we report the first measurement of the midrapidity net-proton C6/C2 from 27, 54.4, and 200 GeV Au+Au collisions at the Relativistic Heavy Ion Collider (RHIC). The dependence on collision centrality and kinematic acceptance in (pT, y) are analyzed. While for 27 and 54.4 GeV collisions the C6/C2 values are close to zero within uncertainties, it is observed that for 200 GeV collisions, the C6/C2 ratio becomes progressively negative from peripheral to central collisions. Transport model calculations without critical dynamics predict mostly positive values except for the most central collisions within uncertainties. These observations seem to favor a smooth crossover in the high-energy nuclear collisions at top RHIC energy. © 2021 American Physical Society.
Keywords: Au+Au collisions; Colliding beam accelerators; Cumulants; First principles; Germanium alloys; Germanium compounds; Gold compounds; Hadronic matters; Heavy ions; Lattice QCD calculations; Measurements of; Mid-rapidity; Multiplicity distributions; Quantum theory; Quark-gluon plasma; Uncertainty; dept.phy; peer-reviewed

Global Λ-hyperon polarization in Au+Au collisions at √sNN = 3 GeV - STAR Collaboration (Physical Review C, 2021)
Global hyperon polarization, P¯H, in Au+Au collisions over a large range of collision energy, sNN, was recently measured and successfully reproduced by hydrodynamic and transport models with intense fluid vorticity of the quark-gluon plasma. While naïve extrapolation of data trends suggests a large P¯H as the collision energy is reduced, the behavior of P¯H at small sNN¡7.7 GeV is unknown. Operating the STAR experiment in fixed-target mode, we measured the polarization of Λ hyperons along the direction of global angular momentum in Au+Au collisions at sNN=3 GeV. The observation of substantial polarization of 4.91±0.81(stat.)±0.15(syst.)% in these collisions may require a reexamination of the viscosity of any fluid created in the collision, of the thermalization timescale of rotational modes, and of hadronic mechanisms to produce global polarization. © 2021 American Physical Society.
Keywords: dept.phy; peer-reviewed